A Case of Sudden Death in Decameron IV.6: Aortic Dissection or Atrial Myxoma?. Issue 2 (8th July 2016) - Toscano, Fabrizio; Spani, Giovanni; Papio, Michael; Rühli, Frank J.; Galassi, Francesco M.
Abstract : Giovanni Boccaccio's Decameron contains a novella that details the sudden death of a young man called Gabriotto, including a portrayal of the discomfort that the protagonist experienced and a rudimentary autopsy performed by local physicians. The intriguing description of symptoms and pathologies has made it possible to read a 7-century-old case through the modern clinical lens. Thanks to the medical and philological analysis of the text—despite the vast difference between modern and medieval medicine—2 hypothetical diagnoses have emerged: either an aortic dissection or an atrial myxoma.